FORMATION OF THE KNOWLEDGE BASE FOR POSTGRADUATE STUDIES ON SPECIALITY «EPIDEMIOLOGY» BASED ON THE COMPETENCY-BASED APPROACH - Беседина, Е. И.; Мельник, В. А.; Лыгина, Ю. А.; Коцюрба, А. Р.; Лыгин, А. Б. (University Clinic; No 3(28) (2018): UNIVERSITY CLINICDO - 10.26435/uc.v0i3(28).198, 2018)
The article presents information based on the experience of teaching the discipline «Epidemiology» to students of faculty of internship and postgraduate studies at the Department of Higher Education, Health Management and Epidemiology. The requirements for the professional education of young specialists are formed according to the need for practical Healthcare Service in the formation of new knowledge, professional skills, and increase in their official duties. In this regard, there is an urgent need to change the traditional process of training graduates (medical residents, interns, etc.) who do not have practical experience to competency-oriented.